Design, preparation and characterization of ulvan based thermosensitive hydrogels. (20th January 2016) - Morelli, Andrea; Betti, Margherita; Puppi, Dario; Chiellini, Federica
Highlights: Exploitation of waste algal biomass as source of ulvan sulphated polysaccharide. p(NIPAAm) grafted onto ulvan acrylate macroinitiator by radical polymerization. Thermosensitive ulvan-based hydrogels by using UV light by a straightforward method. Thermogelling properties feasible as in-situ hydrogel for biomedical applications. Abstract: The present study is focused on the exploitation and conversion of sulphated polysaccharides obtained from waste algal biomass into high value added material for biomedical applications. ulvan, a sulphated polysaccharide extracted from green seaweeds belonging to Ulva sp. was selected as a suitable material due to its chemical versatility and widely ascertained bioactivity. To date the present work represents the first successful attempt of preparation of ulvan-based hydrogels displaying thermogelling behaviour. ulvan was provided with thermogelling properties by grafting poly( N -isopropylacrylamide) chains onto its backbone as thermosensitive component. To this aim ulvan was properly modified with acryloyl groups to act as macroinitiator in the radical polymerization of N -isopropylacrylamide, induced by UV irradiation through a "grafting from" method. The thermogelling properties of the copolymer were investigated by thermal and rheological analyses. Sol–gel transition of the copolymer was found to occur at 30–31 °C thus indicating the feasibility of ulvan for being used as in-situ hydrogel forming systems for biomedical applications.